Double Diabetes; A Case Report - Gupta, Shivangi; Abhishek, Dr.; Athwal, Pal Satyajit Singh; Puri, Piyush; Kem, Anil Kumar (Asian Journal of Medical Research, 2018)
Double diabetes is a new variant which is a combination of both type 1 and type 2 diabetes in children and adolescents. This variant is becoming more prevalent because of epidemic obesity in children. Obesity among people of different ethnicity and race is tripled since last decade. Although, obesity is linked to diabetes type 2 because of insulin resistance which is due to excess free fatty acids, high intracellular triglyceride and dysregulation of adipokines secretion. Double diabetes is coexistence of insulin resistance (type 2) and autoantibodies (type1). Person with type 1 diabetes who is obese and develop type 2 diabetes will lead to increase morbidity and early exhaustion of beta cells. We report a case of 25-year-old male with this new variant discussing diagnosis and management modalities.